2019
DOI: 10.1128/msystems.00289-19
|View full text |Cite|
|
Sign up to set email alerts
|

Altered Fecal Small RNA Profiles in Colorectal Cancer Reflect Gut Microbiome Composition in Stool Samples

Abstract: Dysbiotic configurations of the human gut microbiota have been linked to colorectal cancer (CRC). Human small noncoding RNAs are also implicated in CRC, and recent findings suggest that their release in the gut lumen contributes to shape the gut microbiota. Bacterial small RNAs (bsRNAs) may also play a role in carcinogenesis, but their role has been less extensively explored. Here, we performed small RNA and shotgun sequencing on 80 stool specimens from patients with CRC or with adenomas and from healthy subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 70 publications
(105 reference statements)
3
78
0
1
Order By: Relevance
“…2 and in Supplementary Table 2, show that bacteria biodiversity between the two groups is greatly different. The information obtained is in agreement with those reported in a recently paper from Tarallo et al ( 2019 ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…2 and in Supplementary Table 2, show that bacteria biodiversity between the two groups is greatly different. The information obtained is in agreement with those reported in a recently paper from Tarallo et al ( 2019 ).…”
Section: Resultssupporting
confidence: 93%
“…In particular, bacteria belonging to Bacteroidetes phylum was recently reviewed for its role in metabolic disease, among which Prevotella assumes an important meaning (Johnson et al 2017 ). Likewise, Proteobacteria phylum such as Helicobacter pylori , Desulfovibrio vulgaris , Desulfovibrio fairfieldensis, Desulfovibrio desulfuricans , Escherichia fergusonii , and Haemophiilus parainfluenzae are higher in pathophysiological gut status according to our heat map results and previous studies (Tarallo et al 2019 ; Rizzatti et al 2017 ). Additionally, Libby et al (2019) pointed out a significant correlation for fecal blood presence and the increasing risk of dying from circulatory, respiratory and digestive diseases (excluding colorectal cancer) as well as neuropsychological, blood and endocrine disease (Walker 1990 ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Selected human and animal studies clearly showed the existence of communication axes between the intestine and other organs that are extended beyond the gut, and that contribute to the function and dysfunction of distant organ systems [125,126]. Gut microbiome dysbiosis has been correlated with several types of tumors, suggesting the direct connection between the microbiota and tumor proliferation [127,128].…”
Section: Mammalsmentioning
confidence: 99%
“…Fecal miRNAs have been shown to correlate with tumor stage [ 76 , 77 ], probably because they are continuously released into the intestinal lumen by CRC cells and can be detected in stool samples [ 78 ]. Stool comes into direct contact with the intestinal lumen, providing a rationale for the use of miRNAs as biomarkers in CRC [ 79 ].…”
Section: Micrornamentioning
confidence: 99%